Stator Flux Oriented Control of Three-Phase Induction Motor with Improved Decoupling Scheme - Irvan Arif; Bernadeta Wuri Harini; Feri Yusivar (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
This paper proposes an improved decoupling scheme of stator flux-oriented control for three-phase induction motor. The simulation software used in this paper is MATLAB Simulink®. The result of the simulation indicates that this stator flux-oriented control can control the speed of the rotor angle and stator magnetization current successfully. The angular velocity of 120 rad/s achieved by settling time 2 seconds in critically-damped response and steady-state error 0.083%. The controller can overcome the external disturbance in the form of load torque of 5 Nm which has been simulated in this paper. The proposed stator voltage decoupling scheme which is used in this simulation is correct and become one of success factor of this control method.